Bacillus spp. Contamination: A Novel Risk Originated From Animal Feed to Human Food Chains in South-Eastern Bangladesh - Haque, Md Atiqul; Wang, Fei; Chen, Yi; Hossen, Foysal; Islam, Md Aminul; Hossain, Md Amzad; Siddique, Naila; He, Cheng; Ahmed, Firoz (Frontiers in Microbiology, 2022)
The current study provides information on Bacillus spp. contamination in feed and food chain and present status in commercially available poultry and animal feeds and animal-derived products in Bangladesh. Of 180 different feeds, milk, egg and human stool samples, 218 Bacillus spp. isolated and identified by cultural morphology, microscopic, biochemical and molecular characteristics where B. cereus, B. subtils, B. amylolequefaciens, B. licheniformis, B. thuringiensis, B. megaterium and B. coagulans accounting for 51.3%, 22.4%, 9.1%, 5.9%, 5.0%, 3.6% and, 2.2% respectively. Regarding the enumeration of Total Viable Count (TBC) and Total Bacillus Count (TBC), 67.7% and 39.4% samples were found to contaminate with above 10,000 CFU/g, while highest contamination was 85.5% and 75.0% in broiler feed, respectively. According to a hospital-based survey conducted from 2019 to 2020, food-borne Bacillus spp. contributed 4.5% human diarrhea cases and 25.6% food contamination linked to contaminated regular consuming diets attributing vegetables, rice, RE food, milk and egg were 46%, 34%, 14%, 4% and 2%, respectively. B. cereus was the dominant isolates accounting for 56% and 51.6% egg and milk contamination respectively followed by B. amylolequefaciens (32%), B. thuringiensis (12%) in egg and B. subtilis (25.8%), B. amylolequefaciens (12.9%), B. thuringiensis (6.4%) and B. coagulans (3.2%), in milk respectively. Toxin gene profiling of Bacillus spp. revealed that B. cereus constituted a principal part of virulence, and B. thuringiensis, B. licheniformis, B. megaterium, B. coagulans and B. subtilis showing genetic diversity while B. amylolequefaciens had not carry any toxin gene. Detection rate of enterotoxin genes showed that 55.9% isolates carried nheABC, 71.1% cytK, 80.2% entFM, whereas only 33.4% of the isolates contained hblACD gene cluster posing a threat to human health because this foodborne pathogen can spread across the food and feed chain. Finally, our findings support the hypothesis that B. cereus might be contributed to clinical diarrhea, gizzard erosion and lung infection in duck and poultry, resulting in toxicity and antibacterial resistance to humans. Therefore, maximal tolerance limits of Bacillus spp. and other potential risk are urgently needed to investigate for animal industry. Moreover, toxins-induced food risk is altered for human health via food chain transmission.